A critical review of one-stage anammox processes for treating industrial wastewater: Optimization strategies based on key functional microorganisms. (October 2018) - Li, Jianwei; Li, Jialin; Gao, Ruitao; Wang, Ming; Yang, Lan; Wang, Xiaoling; Zhang, Liang; Peng, Yongzhen
Graphical abstract: Highlights: Optimized strategies of stable operation for anammox process were summarized. Applying granular sludge and biofilms favors retention of anammox biomass. Achieving well performance by coordinating the activity of AOB and AnAOB. Restraining NOB to avoid the deterioration of nitrogen removal performance. Competition, synergy and cooperation between denitrification and anammox. Abstract: The one-stage nitritation/anammox (anaerobic ammonium oxidation) process is an energy-saving technology, which has been successfully developed and widely applied to treat industrial wastewaters. For the one-stage nitritation/anammox process, key functional microbes generally include anaerobic ammonia oxidation bacteria (AnAOB), ammonia-oxidizing bacteria (AOB), nitrite oxidizing bacteria (NOB), and heterotrophic bacteria (HB). Cooperation and competition among the key functional microbes are critical to the stability and performance of anammox process. Based upon key functional microorganisms, this review summarizes and discusses the optimized strategies that promote the operation of one-stage nitritation/anammox process. In particular, the review focuses on strategies related to: (1) the retention of anammox biomass through granular sludge or biofilm, (2) the balanced relationship between AOB and AnAOB, (3) the NOB suppression and (4) the HB management by controlling the influent organic matter. In addition, the review proposes further research to address the existing challenges.